Pengembangan Sistem Informasi Manajemen Stok Barang Berbasis Web Untuk Meningkatkan Akurasi Pengelolaan Inventaris - Mohammad Aditya Nugroho; Arief Hermawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Manual inventory management often leads to various issues such as inaccurate recordkeeping, delays in procurement processes, and difficulties in monitoring stock levels in real time [9]. This study aims to develop a web- and mobile-based inventory management information system using the Waterfall method. The web system was developed using PHP and MySQL, while the mobile application was built using Flutter to provide flexible access for users. The main features of the system include recording incoming and outgoing goods, real-time stock monitoring, and automatic notifications when stock reaches a minimum threshold. The test results indicate significant performance improvements compared to the previous manual process. Based on quantitative evaluation, the accuracy of stock recording increased from 82% to 98% after implementing the system, while the time required to complete stock recap activities was reduced from an average of 45 minutes to 12 minutes per session. In addition, the automatic notification feature accelerated the procurement process—from an average of 6 hours after stock depletion to only 1–2 hours for follow-up actions. Blackbox testing also confirmed that all system functions operated correctly under both normal and error scenarios. With this system, inventory management becomes more structured, accurate, and efficient, supporting faster and data-driven decision-making.